2011
DOI: 10.1016/j.jom.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Imperatives of the science of operations and supply‐chain management

Abstract: a b s t r a c tAlthough knowledge in operations and supply-chain management (O&SCM) has advanced substantially during the last six decades, our community has not fully utilized the potential for radical innovations. We identify two sets of opportunities for pursuing radical innovations. First, there is an opportunity to pursue all phases of science, including exploratory and qualitative research, developing theories, causation and internal validity, and testing models and theories for external validity (the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 60 publications
5
70
0
2
Order By: Relevance
“…It also aligns with the view that organizations are complex systems and that real-world problems involve different departments (Singhal & Singhal, 2012).…”
Section: Conclusion and Research Implicationssupporting
confidence: 66%
See 1 more Smart Citation
“…It also aligns with the view that organizations are complex systems and that real-world problems involve different departments (Singhal & Singhal, 2012).…”
Section: Conclusion and Research Implicationssupporting
confidence: 66%
“…Lee et al (1997b) stresses actions to reduce the bullwhip effect must be evaluated considering the advantages and disadvantages for both players. Singhal and Singhal (2012) claims that organizations are complex and must be approached as a system and that real-world problems usually involve different areas in the company. Therefore, academic research, to be useful for managers, must also cross discipline boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…If the contagion is not stopped, the disease spreads and it can become pandemic. This is supported by Singhal and Singhal (2012) who cite a Washington Post article (Heal and Kunreuther, 2010) calling for firms to understand interconnectedness and how a disruption in an obscure branch of the supply chain could bring the entire system to its knees. In other words, compounding effects will increase supply chain disruption propagation.…”
Section: Compounding Effectsmentioning
confidence: 99%
“…A large number of studies have therefore employed DEA to evaluate logistics providers [36][37][38][39][40][41]. Singhal and Singhal [42] described the usage of DEA for purposes of supply chain management. They indicated that DEA could identify DMUs on an efficiency frontier.…”
Section: Proposed Data Envelopment Analysis Methodsmentioning
confidence: 99%